2015
DOI: 10.1007/s13314-015-0182-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analyses of the Fusarium graminearum species complex isolated from soybean in Argentina and Brazil

Abstract: Soybean is one of the most economically important crops in Argentina and Brazil. However, there is limited information on the biodiversity of the FGSC from soybean as compared to other crops of large-scale growing such as wheat and maize. A phylogenetic recognition of the Fusarium graminearum species complex (FGSC) isolated from soybean in Argentina and Brazil was performed in order to identify species responsible for trichothecene production. Sequences of genes encoding for the partial translation elongation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Species within the FGSC can remain in the soybean stubble and infect the sorghum grain in the next season. Fusarium graminearum is frequently isolated from soybean crops in Argentina . Burgess et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species within the FGSC can remain in the soybean stubble and infect the sorghum grain in the next season. Fusarium graminearum is frequently isolated from soybean crops in Argentina . Burgess et al .…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium graminearum is frequently isolated from soybean crops in Argentina. 30,31 Burgess et al 32 proposed that sorghum only acts as an asymptomatic host of F. graminearum, but this condition can be a toxicological risk, since this species has the potential to produce deoxynivalenol (DON), 15-acetyldeoxynivalenol (15-ADON), 3-acetyldeoxynivalenol (3-ADON), nivalenol (NIV) and zearalenone (ZEA). 33 Navi et al 34 and Balota 35 showed that the infection of sorghum by species within the FGSC caused reduction of kernel germination, mass, density and nutritional and storage quality of the grains.…”
Section: Discussionmentioning
confidence: 99%
“…2010; Chiotta et al . 2015a,b). However, no study has evaluated the survival of the FGSC on soybean residues.…”
Section: Introductionmentioning
confidence: 97%
“…In Argentina, previous studies have shown that species within the FGSC are important fungal pathogens in wheat and soybean crops (Ramirez et al 2007;Barros et al 2012;Chiotta et al 2015a). These crops are commonly used in rotation under conservation cropping systems including no-till systems which provides higher yields (Lori et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation